Model Komunikasi Strategis Religious Leader dalam Pengurangan Stigma dan Diskriminasi Covid-19 - Sholeh Bahrudin; Misbakhul Munir; Siti Aisyatur Rohmah; Ima Nur Saidah; Alifiyah Nurrochmani; Zainul Ahwan (IAI Darussalam, 2021)
This research aims to find a strategic communication model for religious leaders in reducing the stigma and discrimination of Covid-19 in Pasuruan. This research uses descriptive qualitative research. The subjects of this research are opinion leaders and the object of this research is FBO (Faith Based Organization) or religious organizations in Pasuruan. The method in this research uses an interactive model of data analysis with an opinion leader theory approach from Paul Lazarfield. The results of this study indicate that religious leaders (religious leaders) have a strong role in influencing the community in terms of knowledge, attitudes and behavior. Every religious figure becomes an effective communicator in preventing the occurrence of stigma and covid-19 in the community through communication messages in their respective religious pulpits. In addition, the synergy of communication between religious leaders and the government is an effective model in preventing COVID-19 discrimination in the community